2018
DOI: 10.1094/mpmi-01-18-0026-r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Exploration of the Bacterial Type VI Secretion System in Mutualism: Azorhizobium caulinodans ORS571–Sesbania rostrata as a Research Model

Abstract: The bacterial type VI secretion system (T6SS) has been considered the armed force of bacteria because it can deliver toxin effectors to prokaryotic or eukaryotic cells for survival and fitness. Although many legume symbiotic rhizobacteria encode T6SS in their genome, the biological function of T6SS in these bacteria is still unclear. To elucidate this issue, we used Azorhizobium caulinodans ORS571 and its symbiotic host Sesbania rostrata as our research model. By using T6SS gene deletion mutants, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Recently, it was reported that R. etli Mim1 T6SS mutant produced plants with lower dry weight and smaller nodules than the wild-type strain, suggesting for the first time a positive role of T6SS in Rhizobium-legume symbiosis (Salinero-Lanzarote et al, 2019). The rhizobacterium Azorhizobium caulinodans ORS571 utilizes its T6SS to outcompete other strains during infection of its host Sesbania rostrata (Lin et al, 2018). However, the researchers could not show involvement in inter-bacterial competition in vitro.…”
Section: Root-nodulating Bacteriamentioning
confidence: 97%
“…Recently, it was reported that R. etli Mim1 T6SS mutant produced plants with lower dry weight and smaller nodules than the wild-type strain, suggesting for the first time a positive role of T6SS in Rhizobium-legume symbiosis (Salinero-Lanzarote et al, 2019). The rhizobacterium Azorhizobium caulinodans ORS571 utilizes its T6SS to outcompete other strains during infection of its host Sesbania rostrata (Lin et al, 2018). However, the researchers could not show involvement in inter-bacterial competition in vitro.…”
Section: Root-nodulating Bacteriamentioning
confidence: 97%
“…Interbacterial competition activity mediated by T6SS‐secreted toxins has been described for some soil bacteria as Agrobacterium tumefaciens or Pseudomonas putida (Bondage et al ., 2016; Bernal et al ., 2017). Despite the available information on T6SS and related toxin‐immunity protein pairs in different rhizobial strains (Bondage et al ., 2016; Bernal et al ., 2018; Salinero‐Lanzarote et al ., 2019; Zalguizuri et al ., 2019), a role for rhizobial putative T6SS toxins in interbacterial competition has not been demonstrated thus far (Lin et al ., 2018). Another type of interbacterial toxins is bacteriocins (Holtsmark et al ., 2008).…”
Section: Mechanisms Behind the Limitations Of The Nodulation Process And Bacterial Tools To Overcome Themmentioning
confidence: 99%
“…In addition to the T3SS, other bacterial protein secretion systems have been described as having a role in the symbiotic process: type IV and type VI secretion system (T4SS and T6SS respectively) (Nelson and Sadowsky, 2015;Lin et al, 2018;Salinero-Lanzarote et al, 2019). In M. japonicum R7A, T4SS has an analogous role to that attributed to T3SS in M. japonicum MAFF303099 (Hubber et al, 2004).…”
Section: Plant Defence Responsementioning
confidence: 99%
“…Since then, a few researchers have studied the role of T6SS in symbiosis beyond mentioning its presence. In two such studies, it was found that mutations in T6SS genes do not affect symbiotic efficiency but symbiotic competitiveness (De Campos et al, 2017;Lin et al, 2018), and in another study, a positive effect on symbiosis was demonstrated (Salinero-Lanzarote et al, 2019).…”
Section: Type VI Secretion System (T6ss) In Rhizobiamentioning
confidence: 99%